Na-Ce-modified-SBA-15 as an effective and reusable bimetallic mesoporous catalyst for the sustainable production of biodiesel - Sánchez Faba, Edgar Maximiliano (2020)
With the purpose to compete with the homogeneous catalytic biodiesel production, a highlyefficient bimetallic solid catalyst with high exposed surface, high basicity, and reusablethroughout several reaction cycles, was developed by doping SBA-15 with sodium and cerium indifferent concentrations. The catalyst with 5 wt% of sodium and 20 wt% of cerium showed goodstructural ordering and had the highest basicity due to the presence of a large amount of mediumand strong sites compared to the other materials. It was effectively used as a solid base catalystfor biodiesel production from sunflower oil and absolute methanol. The highest FAME content(98.9 wt%) was achieved under optimum conditions of 40:1 methanol/oil molar ratio, 10 wt%catalyst loading, 60 °C, stirring speed of 600-700 rpm and 180 min. Further, this material wasreused for five consecutive runs, obtaining FAME contents greater than 90% in each one of them.